Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.7150/thno.60031
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic YAP protects the optic nerve and retina in an experimental autoimmune encephalomyelitis model through TGF-β signaling

Abstract: Rationale: Optic neuritis is one of main symptoms in multiple sclerosis (MS) that causes visual disability. Astrocytes are pivotal regulators of neuroinflammation in MS, and astrocytic yes-associated protein (YAP) plays a critical role in neuroinflammation. Meanwhile, YAP signaling is involved in visual impairment, including glaucoma, retinal choroidal atrophy and retinal detachment. However, the roles and underlying mechanisms of astrocytic YAP in neuroinflammation and demyelination of MS-related o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 78 publications
0
27
0
Order By: Relevance
“…Optic nerve is the main transmission pathway of visual information. ON damage can be caused by craniocerebral injury, inflammation, high intraocular pressure, and tumor growth [ 1 ]. ON is also a common optic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optic nerve is the main transmission pathway of visual information. ON damage can be caused by craniocerebral injury, inflammation, high intraocular pressure, and tumor growth [ 1 ]. ON is also a common optic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Optic neuritis (ON) refers to various inflammatory lesions of the optic nerve, which is a more common optic nerve disease in young people [ 1 ]. According to the etiology, it can be divided into idiopathic optic neuritis, infectious and infection-related optic neuritis, autoimmune optic neuritis, and other optic neuritis that cannot be classified [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of YAP by XMU‐MP‐1, a pharmacological inhibitor of MST1/2, induced the expression of HMGCS1 in astrocytes, inhibited demyelination and neuroinflammation, and enhanced the functional recovery in EAE mice [124]. A similar role of YAP has been explored in optic neuritis, another crucial feature in multiple sclerosis [125]. Activated YAP in astrocytes of optic nerve prevents demyelination and neuroinflammation in EAE mice through TGF‐β pathways.…”
Section: Hippo Signaling Pathway In Neuroinflammationmentioning
confidence: 99%
“…Conditional deletion of YAP in astrocytes exacerbated inflammatory microglia infiltration and demyelination process (Fig. 6), which was associated with the loss of retinal ganglion cells in EAE mice [125].…”
Section: Hippo Signaling Pathway In Neuroinflammationmentioning
confidence: 99%
“…Recent reports have shown that YAP is upregulated and activated in astrocytes through suppression of the Hippo pathway after spinal cord injury, and promotes glial scar formation and neural regeneration, and improves functional recovery of mice after SCI [ 41 ]. Also, our recent research has shown that astrocytic YAP could prevent the demyelination and neuroinflammation of the retina and optic nerve of EAE through upregulating TGF-β signaling [ 53 ]. Interestingly, consistent with these previous studies, present studies showed that in EAE mice, YAP was also upregulated and activated through suppression of Hippo pathway in astrocytes, not in microglia or neurons of spinal cords (Fig.…”
Section: Discussionmentioning
confidence: 99%